Upregulation of Proinflammatory Variables of Analytical Importance and their Potential Interplay in the Pathogenesis of Rheumatoid Arthritis - Khalida Anwar, Anoosh Qayyum, Amina Shahid, Nusrat Tariq, Sultan Ahmad, Naveed Shuja, Sara Zahid, Sulayman Waquar, Arif Malik, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Study role of the selected inflammatory markers and their importance in the development and progression of rheumatoid arthritis. Study Design: Cross-sectional study Place and Duration: Institute of Molecular Biology and Biotechnology, The University of Lahore, (11-months) Methodology: A total of 50 patients diagnosed with rheumatoid arthritis in the Department of Orthopedics (Allama Iqbal Medical College, Jinnah Hospital, Lahore-Pakistan) and 50 healthy individuals of the age of 35-45 were included into the study. Glutathione, Catalase, Maliondialdehyde, Superoxide dismutase, Glutathione peroxidase, Nitric oxide (NO) and vitamin C, E and A was estimated spectrophotometrically. Serum C-Reactive Protein, IL-21, TNF-α, AOPPs, AGE’s and MMP-3 was measured by ELISA method using Human-ELISA kits (Glory) Results: A statistically noteworthy raise of all the biomarkers level in serum of rheumatoid arthritis (RA) was seen (p=0.001) comparable with healthy individuals. The correlation between joint damage progression diagnostic biomarker AGE and MMP-3 levels (r=0.485, 95% p=0.001) was highly significant. CRP and IL-21 also showed highly significant raise in joint inflammation (r=0.359, p=0.001). The results significantly depicted that model of MMP-3 levels at the onset of the disease and CRP and IL-21 were the robust interpreters of the erosion development. Similarly, antioxidants including Vitamin E, Vitamin C and Vitamin A were decreased in levels of (p<0.011), (p<0.011) and (p<0.022) respectively in RA subjects than in control subjects. Vitamin E, C and A are the most imperative free radical foragers within membrane. They also act as the major line of resistance against free radicals. Conclusion: Development of pain in joints in rheumatoid arthritis condition is due to the increase in the oxidative stress which is the key contrivance in the pathogenesis of RA. Keyword: Reactive oxygen species, Oxidative stress, oxidation of lipid peroxides, Rheumatoid arthritis, Osteoarthritis, osteocyte damage.